THE MEDIATING ROLE OF CUSTOMER FINANCIAL BEHAVIOR IN INSTALLMENT PAYMENT BEHAVIOR AT ISLAMIC BANKS IN GREATER BANDUNG - Benny Kurniawan; Ira Novianty; Marwansyah (JAT : Journal Of Accounting and Tax, 2026)
The study employs an explanatory quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data collected from 211 retail financing customers across five Islamic Commercial Banks operating in Greater Bandung: Bank BSI, Bank BSN, Bank Muamalat, Bank BJB Syariah, and Bank BTPN Syariah. Respondents were selected through purposive sampling based on criteria including active financing status, minimum 12-month customer tenure, and residence within the Greater Bandung area. The findings reveal three key results. First, Islamic financial literacy has a direct positive and significant effect on installment payment behavior (t = 3.191, p = 0.001), confirming that customers with stronger understanding of contract structures, margin calculations, and debt management demonstrate better payment discipline. Second, customer ethics does not directly influence installment payment behavior (t = 1.418, p = 0.156), suggesting that moral values alone are insufficient to ensure payment compliance without behavioral transformation. Third, customer financial behavior fully mediates the relationship between customer ethics and installment payment behavior (t = 3.276, p = 0.001), while it does not mediate the literacy–payment behavior relationship (t = 1.866, p = 0.062). The structural model explains 79.4% of the variance in installment payment behavior (R² = 0.794) and 76.2% of customer financial behavior variance (R² = 0.762. The study is limited to the Greater Bandung retail financing context and cross-sectional self-report data; future research should extend to other regions and financing segments using longitudinal designs.